Administrative strategies of the principal on the academic performance of students in Public Secondary Schools in Imo State - Obinna, Ajuzie Cosmas (Universitas Ahmad Dahlan, 2025)
This study examined staffing/staff development, provision of learning materials, and motivation of teachers as administrative strategies of principals on the academic performance of students in public secondary schools in Imo State. It employed a survey design. Three research questions were posed, while two hypotheses were formulated and tested at the 0.05 level of significance. Hypothesis one showed that there is no significant difference in the mean rating of the responses of principals and teachers on the examined staffing on students’ academic performance. The second hypothesis showed that there is no significant difference between the mean perception of principals and teachers on the examined staff development on the academic performance of students. The population comprised twenty-six thousand two hundred and eighteen (26,218) teachers, principals, and students from public secondary schools in the 270 secondary schools in Imo State, with a sample size of 2,870 teachers, principals, and students. Data were collected using the “Principals' Administrative Strategies and Students’ Academic Performance Questionnaire (PASSAPQ),